A composite solid electrolyte membrane and preparation method thereof
By using a high pore and large pore diameter polyolefin microporous membrane and a tight body composite technology of inorganic solid electrolyte in the solid electrolyte membrane, combined with ultrasonic oscillation and far-infrared drying, the problem of high brittleness and hardness after processing and forming is solved, the combination of high mechanical strength and high conductivity is achieved, and the energy density and circulation life of the battery are improved.
Patent Information
- Application Number
- CN202510031356.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The existing solid electrolyte membrane has high brittleness and hardness after processing and forming, resulting in poor interfacial compatibility with the positive and negative electrodes, and it is difficult to achieve both high conductivity and high mechanical strength.
A high-pore large-pore polyolefin microporous film is used as the matrix, and the solid electrolyte slurry is prepared in a high-speed mixer. Combined with ultrasonic oscillation and far-infrared drying technology, the inorganic solid electrolyte and the tight body of the polyolefin microporous film are realized, and the voids are filled with sodium polyacrylate binder to enhance adhesion.
The high mechanical strength and high room temperature ionic conductivity of the solid electrolyte membrane are achieved, the matrix thickness is reduced, the interface compatibility with the positive and negative electrodes is improved, and the energy density and circulation life of the battery are enhanced.
Smart Images

Figure CN119447429B_ABST
Abstract
Description
Technical Field
[0001] The invention discloses a method for preparing a composite solid electrolyte membrane, and belongs to the technical field of new energy materials. Background Art
[0002] With the development of science and technology, the transformation of lithium-ion battery electrolyte from liquid to solid is the current major technological trend. On the one hand, solid electrolyte replaces electrolyte as ion transfer medium, and electrolyte volatilization and leakage will not occur during battery recycling, thus eliminating safety hazards and improving battery life. On the other hand, the energy density of traditional lithium-ion batteries has reached a technical bottleneck. In order to further improve the battery energy density, metal lithium is used to replace the graphite negative electrode in lithium-ion batteries. However, metal lithium has poor compatibility with electrolyte and is prone to form lithium dendrites that pierce the diaphragm during the electrochemical reaction of charge and discharge, causing safety problems. Solid electrolytes replacing traditional liquid electrolytes can improve the above problems to a certain extent.
[0003] Currently, common solid electrolytes are divided into polymer solid electrolytes and inorganic solid electrolytes. Polymer solid electrolytes have the characteristics of good flexibility and easy processing and molding, but their room temperature ionic conductivity is low; inorganic solid electrolytes such as sulfide solid electrolytes, oxide solid electrolytes, and halide solid electrolytes have good room temperature conductivity relative to polymer solid electrolytes, but they are brittle and hard after processing and molding, resulting in poor interface compatibility with the positive and negative electrodes. In view of the above problems, an organic-inorganic composite technical solution can be used in actual production to improve the overall performance of solid electrolytes such as flexibility and electrochemical properties. At present, organic-inorganic composites in the industry are mostly processed by coating or in-situ solidification, but the coating method only coats a layer of inorganic solid electrolyte on the surface of the organic material, which cannot achieve a tight composite of the bulk phase. In actual use, a large amount of liquid electrolyte still needs to be added to improve and ensure its ionic conductivity. Although the in-situ solidification method has achieved the composite of organic-inorganic three-dimensional network bulk phases to a certain extent, due to the generation of by-products in the process, a large amount of airborne particles are still retained between the bulk phases after curing and drying, and if the by-products cannot be completely removed, the cycle life of the battery during the charging and discharging process will be affected to a certain extent. Although there are related studies on immersing the film substrate in the solid electrolyte slurry, such as CN202211107348.1, an expanded polytetrafluoroethylene-enhanced solid electrolyte membrane and its preparation method, the ePTFE porous support is immersed in the solid electrolyte slurry, after an appropriate ultrasonic time, it is pulled upward at a certain speed, and then left to stand and dried to obtain a dense filling, and the conductivity of the solid electrolyte membrane is obtained (2.68×10-4Scm -1), high mechanical strength (9.65MPa), this method has the problems of uneven dispersion of solid electrolyte particles, insufficient density, and inability to achieve high conductivity. At present, the particle size in the solid electrolyte slurry in this field needs to be greater than 100nm to ensure its dispersibility, and the dispersion effect of LATP solid electrolyte below 100nm is poor. The microporous membrane used in the present invention is made by double drawing, which has higher mechanical strength, which can reach more than 20 MPa, and prevents mechanical damage and dendrite puncture during battery assembly, etc., and the microporous membrane has a large pore size, and the gaps can be well filled with oxide solid electrolytes of different particle sizes for more comprehensive bulk composite, and it is not easy to de-powder, so as to achieve higher conductivity. Summary of the invention
[0004] In order to solve the problems in the background technology, the present invention provides a method for preparing a composite solid electrolyte membrane. The present invention prepares an organic-inorganic composite solid electrolyte membrane, which has good mechanical processing performance and good room temperature ionic conductivity, and has good interface compatibility between positive and negative electrodes after lamination.
[0005] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is:
[0006] A method for preparing a composite solid electrolyte membrane, the preparation steps are as follows:
[0007] (1) Preparation of solid electrolyte slurry: Pour 30-50% of the total solvent into a high-speed mixer, start stirring and slowly add the dispersant, stir for 10-15 min, continue stirring and slowly add a certain proportion of small-particle oxide solid electrolyte powder and large-particle oxide solid electrolyte powder, increase the stirring line speed to 25-50 m / s, add the remaining solvent, stir for 30-60 min and set aside.
[0008] (2) Preparation of solid electrolyte membrane: The two ends of the polyolefin microporous membrane are fixed and completely immersed in the above-mentioned solid electrolyte slurry, and ultrasonically vibrated at 35-55°C with a power of 250-300 W for 5-10 min, then taken out, and completely dried at 45-55°C with far-infrared hot air, the far-infrared power is 200-300 W, and the irradiation distance is 30-50 cm to obtain intermediate A. Intermediate A is further immersed in a binder solution containing 0.5-5%, ultrasonically vibrated for 2-5 min, and then taken out and continued to be completely dried in a far-infrared hot air environment at 45-55°C.
[0009] Furthermore, the proportions of the materials in the solid electrolyte slurry are 20-30% oxide solid electrolyte, 0.5-4.0% dispersant, and the rest is solvent, totaling 100%. Among them, the small-particle oxide solid electrolyte powder accounts for 5-10% of the total mass of the oxide solid electrolyte powder, and the rest is large-particle oxide solid electrolyte powder.
[0010] Furthermore, the polyolefin microporous membrane has a pore size range of 300-5000 nm, a porosity of >65%, and is self-made (prepared by conventional semi-dry method) or commercially available.
[0011] Furthermore, the dispersant is a dispersant containing a quaternary ammonium group, specifically one of BYK-ET3000, BYK-ET3001, BYK-ET3002, BYK-ET3004, or a mixture of two or more thereof.
[0012] Furthermore, the oxide solid electrolyte is a LATP inorganic electrolyte
[0013] Furthermore, the particle size of the small-particle oxide solid electrolyte powder is 50-80 nm, and the particle size of the large-particle oxide solid electrolyte powder is 150-200 nm.
[0014] Furthermore, the solvent is N-methyl-2-pyrrolidone (NMP) or a mixed solvent of NMP and acetone.
[0015] Furthermore, the binder is sodium polyacrylate (PAA) with a molecular weight of 50,000-1,000,000.
[0016] Furthermore, the thickness of the polyolefin microporous membrane is 6-20 μm, and the thickness of the final composite solid electrolyte membrane is 4-18 μm.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The present invention adopts a high-porosity and large-aperture polyolefin microporous membrane as a matrix, which provides a three-dimensional network flexible framework for the solid electrolyte. After the solid electrolytes of different particle sizes are fully and evenly mixed by a dispersant, they can be quickly and smoothly filled into the polyolefin microporous membrane matrix under the action of ultrasound. At the same time, due to the selection of two large and small particle sizes of the solid electrolyte, the small particle size particles can better fill the gap between the large solid electrolyte particles and the matrix, thereby achieving complete fusion between the solid electrolyte and the polyolefin microporous membrane matrix in the bulk phase.
[0019] In the preparation stage of solid electrolyte slurry, the quaternary ammonium groups contained in the dispersant enhance the surface activity of the dispersant, improve the wettability of the inorganic particles, and greatly shorten the dispersion time of small-size inorganic particles. -3The chemical bonding between them can form a good anchor point, which plays a good role in dispersion and stabilization during the stirring process, and promotes the small and large particle sizes of the solid electrolyte to have good uniform dispersion. After the LATP particles of different particle sizes and the polyolefin microporous membrane are well composited under the action of ultrasound, the impregnated sodium polyacrylate PAA binder further fills the gap between the LATP particles and the polyolefin microporous membrane and tightly bonds the inorganic particles to the organic matrix, preventing the composite membrane from falling powder during use. At the same time, hot pressing in the subsequent battery cell manufacturing process can further increase the compactness of the bulk solid electrolyte composite membrane and the interface compatibility with the positive and negative electrodes, which has a good beneficial effect on improving ionic conductivity and energy density.
[0020] Due to the beneficial effects of the above-mentioned technology, the inorganic solid electrolyte and the polyolefin microporous membrane are tightly combined, which reduces the thickness of the matrix in macroscopic performance, making the thickness of the composite solid electrolyte membrane smaller than the thickness of the matrix, and also contributing to beneficial effects in terms of energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a SEM scan of the polyolefin microporous membrane before bulk filling.
[0022] Figure 2 This is a SEM scan of the cross section of the solid electrolyte composite membrane after bulk composite in Example 1.
[0023] Figure 3 This is a SEM scan of the cross-section of the solid electrolyte composite membrane after bulk composite in Comparative Example 2.
[0024] Figure 4 This is a SEM scan of the surface of the solid electrolyte composite membrane after bulk composite in Comparative Example 3.
[0025] Figure 5 This is a SEM scan of the cross-section of the solid electrolyte composite membrane after bulk composite in Comparative Example 3.
[0026] Figure 6 This is a SEM scan of the cross-section of the solid electrolyte composite membrane after bulk composite in Comparative Example 5. DETAILED DESCRIPTION
[0027] In the embodiment, the pore size of the polyolefin microporous membrane is in the range of 300-5000 nm, and the porosity is greater than 65%: it is prepared by conventional semi-dry synchronous stretching. Small-particle LATP inorganic electrolyte (50-80 nm), large-particle LATP inorganic electrolyte (150-200 nm), and sodium polyacrylate PAA are commercially available products.
[0028] Embodiment 1,
[0029] (1) Preparation of solid electrolyte slurry: The proportions of the materials in the solid electrolyte slurry are 20% LATP inorganic electrolyte, 2% BYK-ET3000 dispersant, and the rest NMP solvent, totaling 100%; the small-particle LATP inorganic electrolyte accounts for 6% of the total mass of the solid electrolyte, and the rest is large-particle LATP inorganic electrolyte.
[0030] Pour 30% of the solvent into the high-speed blender in proportion, start stirring and slowly add the dispersant and stir for 10-15 minutes, continue stirring (stirring speed is 15m / s) and slowly add small-particle and large-particle oxide solid electrolyte powders, increase the stirring line speed to 25m / s and add the remaining solvent and stir for 30 minutes before use.
[0031] (2) Preparation of solid electrolyte membrane: The high-pore polyolefin microporous membrane (thickness 18 µm) was fixed at both ends and completely immersed in the above-mentioned solid electrolyte slurry. After ultrasonic oscillation at 35°C with a power of 250 W for 10 min, it was taken out and completely dried at 55°C with far-infrared hot air. The far-infrared power was 200 W and the irradiation distance was 30 cm to obtain intermediate A. The intermediate A was further immersed in a binder solution containing sodium polyacrylate (PAA) with a mass concentration of 0.6% and ultrasonically oscillated for 2-5 min. After that, it was taken out and continued to be dried completely in a far-infrared hot air environment at 45-55°C to obtain a composite solid electrolyte membrane with a thickness of 16.7 µm.
[0032] Embodiment 2,
[0033] (1) Preparation of solid electrolyte slurry: The material ratios in the solid electrolyte slurry are 22% LATP inorganic electrolyte, 2.5% BYK-ET3001 dispersant, and the remainder is a mixed solvent of NMP and acetone, in which NMP accounts for 75% of the total solvent, totaling 100%; the small-particle LATP inorganic electrolyte accounts for 7.5% of the total mass of the solid electrolyte, and the rest is the large-particle LATP inorganic electrolyte.
[0034] Pour 50% of the solvent into the high-speed blender in proportion, start stirring and slowly add the dispersant and stir for 10-15 minutes, continue stirring (stirring speed is 10m / s) and slowly add small-particle and large-particle oxide solid electrolyte powders, increase the stirring line speed to 35m / s and add the remaining solvent and stir for 45 minutes before use.
[0035] (2) Preparation of solid electrolyte membrane: The high-aperture polyolefin microporous membrane (thickness 20 µm) was fixed at both ends and completely immersed in the above-mentioned solid electrolyte slurry. After ultrasonic oscillation at 40°C with a power of 285 W for 10 min, it was taken out and completely dried at 55°C with far-infrared hot air. The far-infrared power was 250 W and the irradiation distance was 50 cm to obtain intermediate A. Intermediate A was further immersed in a sodium polyacrylate binder solution containing a mass concentration of 1.2% and ultrasonically oscillated for 2-5 min. After that, it was taken out and continued to be dried completely in a far-infrared hot air environment at 45-55°C to obtain a composite solid electrolyte membrane with a thickness of 17.9 µm.
[0036] Embodiment 3,
[0037] (1) Preparation of solid electrolyte slurry: The material ratios in the solid electrolyte slurry are 25% LATP inorganic electrolyte, 1.5% BYK-ET3000, 0.5% BYK-ET3002, and the rest is NMP solvent, totaling 100%; the small-particle LATP inorganic electrolyte accounts for 8.0% of the total mass of the solid electrolyte, and the rest is large-particle LATP inorganic electrolyte.
[0038] Pour 40% of the solvent into the high-speed blender in proportion, start stirring and slowly add the dispersant and stir for 10-15 minutes, continue stirring (stirring speed is 8 m / s) and slowly add small-particle and large-particle oxide solid electrolyte powders, increase the stirring line speed to 50 m / s and add the remaining solvent and stir for 60 minutes before use.
[0039] (2) Preparation of solid electrolyte membrane: The high-pore polyolefin microporous membrane (thickness 16 µm) was fixed at both ends and completely immersed in the above-mentioned solid electrolyte slurry. The membrane was ultrasonically vibrated at 55°C with a power of 300 W for 10 min, then taken out and dried completely at 45°C with far-infrared hot air. The far-infrared power was 300 W and the irradiation distance was 35 cm to obtain intermediate A. The intermediate A was further immersed in a binder solution containing 2.5% sodium polyacrylate (PAA) and ultrasonically vibrated for 2-5 min. The membrane was taken out and dried completely in a far-infrared hot air environment at 45-55°C to obtain a composite solid electrolyte membrane with a thickness of 15.1 µm.
[0040] Embodiment 4,
[0041] (1) Preparation of solid electrolyte slurry: The proportions of the materials in the solid electrolyte slurry are 30% LATP inorganic electrolyte, 1.8% BYK-ET3000, 1.5% BYK-ET3004, and the rest is a mixed solvent of NMP and acetone, of which NMP accounts for 70% of the total solvent, totaling 100%; the small-particle LATP inorganic electrolyte accounts for 10.0% of the total mass of the solid electrolyte, and the rest is the large-particle LATP inorganic electrolyte.
[0042] Pour 40% of the solvent into the high-speed blender in proportion, start stirring and slowly add the dispersant and stir for 10-15 minutes, continue stirring (stirring speed is 20m / s) and slowly add small-particle and large-particle oxide solid electrolyte powders, increase the stirring line speed to 40m / s and add the remaining solvent and stir for 50 minutes before use.
[0043] (2) Preparation of solid electrolyte membrane: The high-pore polyolefin microporous membrane (thickness 12 µm) was fixed at both ends and completely immersed in the above-mentioned solid electrolyte slurry. After ultrasonic vibration at 50°C and a power of 280 W for 8 min, it was taken out and completely dried at 45°C with far-infrared hot air. The far-infrared power was 210 W and the irradiation distance was 38 cm to obtain intermediate A. Intermediate A was further immersed in a binder solution containing 1.5% sodium polyacrylate (PAA) by mass and ultrasonically vibrated for 2-5 min. After that, it was taken out and continued to be dried completely in a far-infrared hot air environment at 45-55°C to obtain a composite solid electrolyte membrane with a thickness of 10.6 µm.
[0044] Embodiment 5,
[0045] (1) Preparation of solid electrolyte slurry: The material ratios in the solid electrolyte slurry are 28% LATP inorganic electrolyte, 2.5% BYK-ET3004, and the rest is a mixed solvent of NMP and acetone, in which NMP accounts for 80% of the total solvent, totaling 100%; the small-particle LATP inorganic electrolyte accounts for 5.0% of the total mass of the solid electrolyte, and the rest is the large-particle LATP inorganic electrolyte.
[0046] Pour 50% of the solvent in proportion into the high-speed blender, start stirring and slowly add the dispersant and stir for 10-15 minutes, continue stirring (stirring speed is 18m / s) and slowly add small-particle and large-particle oxide solid electrolyte powders, increase the stirring line speed to 50m / s and add the remaining solvent and stir for 60 minutes before use.
[0047] (2) Preparation of solid electrolyte membrane: The high-pore polyolefin microporous membrane (thickness 14 µm) was fixed at both ends and completely immersed in the above-mentioned solid electrolyte slurry. After ultrasonic oscillation at 40°C with a power of 300 W for 10 min, it was taken out and completely dried at 45°C with far-infrared hot air. The far-infrared power was 260 W and the irradiation distance was 45 cm to obtain intermediate A. The intermediate A was further immersed in a binder solution containing 3.8% sodium polyacrylate (PAA) and ultrasonically oscillated for 2-5 min. After that, it was taken out and continued to be dried completely in a far-infrared hot air environment at 45-55°C to obtain a composite solid electrolyte membrane (thickness 12.2 µm).
[0048] Embodiment 6,
[0049] (1) Preparation of solid electrolyte slurry: The material ratios in the solid electrolyte slurry are 22% LATP inorganic electrolyte, 3.5% BYK-ET3000, and the rest NMP solvent, totaling 100%; the small-particle LATP inorganic electrolyte accounts for 8.0% of the total mass of the solid electrolyte, and the rest is large-particle LATP inorganic electrolyte.
[0050] Pour 45% of the solvent into the high-speed blender in proportion, start stirring and slowly add the dispersant and stir for 10-15 minutes, continue stirring (stirring speed is 18 m / s) and slowly add small-particle and large-particle oxide solid electrolyte powders, increase the stirring line speed to 28 m / s and add the remaining solvent and stir for 45 minutes before use.
[0051] (2) Preparation of solid electrolyte membrane: The high-pore polyolefin microporous membrane (thickness 8 µm) was fixed at both ends and completely immersed in the above-mentioned solid electrolyte slurry. After ultrasonic oscillation at 55°C with a power of 300 W for 10 min, it was taken out and completely dried at 55°C with far-infrared hot air. The far-infrared power was 300 W and the irradiation distance was 50 cm to obtain intermediate A. The intermediate A was further immersed in a binder solution containing 3.2% sodium polyacrylate (PAA) and ultrasonically oscillated for 2-5 min. After that, it was taken out and continued to be dried completely in a far-infrared hot air environment at 45-55°C to obtain a composite solid electrolyte membrane (thickness 6.3 µm).
[0052] Embodiment 7,
[0053] (1) Preparation of solid electrolyte slurry: The material ratios in the solid electrolyte slurry are 23% LATP inorganic electrolyte, 2.8% BYK-ET3000, and the rest is a mixed solvent of NMP and acetone, in which NMP accounts for 90% of the total solvent, totaling 100%; the small-particle LATP inorganic electrolyte accounts for 6.5% of the total mass of the solid electrolyte, and the rest is the large-particle LATP inorganic electrolyte.
[0054] Pour 35% of the solvent into the high-speed blender in proportion, start stirring and slowly add the dispersant and stir for 10-15 minutes, continue stirring (stirring speed is 15m / s) and slowly add small-particle and large-particle oxide solid electrolyte powders, increase the stirring line speed to 35m / s and add the remaining solvent and stir for 60 minutes before use.
[0055] (2) Preparation of solid electrolyte membrane: The high-pore polyolefin microporous membrane (thickness 6 µm) was fixed at both ends and completely immersed in the above-mentioned solid electrolyte slurry. After ultrasonic vibration at 45°C with a power of 300 W for 8 min, it was taken out and completely dried at 45°C with far-infrared hot air. The far-infrared power was 300 W and the irradiation distance was 50 cm to obtain intermediate A. The intermediate A was further immersed in a binder solution containing 4.8% sodium polyacrylate (PAA) and ultrasonically vibrated for 2-5 min. After that, it was taken out and continued to be dried completely in a far-infrared hot air environment at 45-55°C to obtain a composite solid electrolyte membrane (thickness 4.2 µm).
[0056] Embodiment 8,
[0057] (1) Preparation of solid electrolyte slurry: The material ratios in the solid electrolyte slurry are 20% LATP inorganic electrolyte, 3.0% BYK-ET3002, and the rest NMP solvent, totaling 100%; the small-particle LATP inorganic electrolyte accounts for 7.8% of the total mass of the solid electrolyte, and the rest is large-particle LATP inorganic electrolyte.
[0058] Pour 50% of the solvent into the high-speed blender in proportion, start stirring and slowly add the dispersant and stir for 10-15 minutes, continue stirring (stirring speed is 15m / s) and slowly add small-particle and large-particle oxide solid electrolyte powders, increase the stirring line speed to 40m / s and add the remaining solvent and stir for 60 minutes before use.
[0059] (2) Preparation of solid electrolyte membrane: The high-pore polyolefin microporous membrane (thickness 16.0 µm) was fixed at both ends and completely immersed in the above-mentioned solid electrolyte slurry. After ultrasonic vibration at 55°C and a power of 290 W for 5 min, it was taken out and completely dried at 48°C with far-infrared hot air. The far-infrared power was 200 W and the irradiation distance was 35 cm to obtain intermediate A. The intermediate A was further immersed in a binder solution containing 0.5% sodium polyacrylate (PAA) and ultrasonically vibrated for 2-5 min. After that, it was taken out and continued to be dried completely in a far-infrared hot air environment at 45-55°C to obtain a composite solid electrolyte membrane (thickness 14.9 µm).
[0060] The solid electrolyte slurry prepared in step (1) of the above examples 1-8 was tested for stability: after the slurry was prepared, it was placed in a beaker for 60 minutes to observe whether there was stratification. If there was, it was NG, and if no stratification was found, it was OK. The particle size distribution of its components was further tested with a laser particle size analyzer and compared with the original particle size to further determine whether it met the requirements.
[0061] The tensile strength and thermal shrinkage test methods of the composite solid electrolyte membrane prepared in Examples 1-8 above were performed in accordance with the corresponding sections of GB / T36363.2018;
[0062] The composite solid electrolyte membrane prepared in the above Examples 1-8 was subjected to conductivity testing: the composite solid electrolyte membrane was clamped into the model using a solid-state battery pressure test mold CN-10 for testing.
[0063] Table 1
[0064]
[0065] Comparative Example 1: Comparative Example 1 is different from Example 1 in that the LATP inorganic electrolytes in Example 1 are all LATP inorganic electrolytes with a particle size of 50 to 80 nm, and the other operations are the same as those in Example 1 to prepare a composite solid electrolyte membrane.
[0066] The solid electrolyte slurry in Comparative Example 1 did not settle, and the conductivity of the final composite solid electrolyte membrane was 0.54 (E -3 s / cm, 25℃).
[0067] Comparative Example 2: Compared with Example 1, Comparative Example 2 differs in that: the LATP inorganic electrolytes in Example 1 are all LATP inorganic electrolytes with a particle size of 150-200 nm, and the other operations are the same as those in Example 1 to prepare a composite solid electrolyte membrane.
[0068] The composite effect of the solid electrolyte membrane in Comparative Example 2 is shown in Figure 3 The cross-sectional SEM observation showed that there were some voids, and the conductivity of the final composite solid electrolyte membrane was 0.46 (E -3 s / cm, 25℃).
[0069] Comparative Example 3: Compared with Example 1, Comparative Example 3 differs in that: the LATP inorganic electrolytes in Example 1 are all LATP inorganic electrolytes with a particle size of 400-700 nm, and other operations are the same as those in Example 1 to prepare a composite solid electrolyte membrane.
[0070] The composite effect of the solid electrolyte membrane in Comparative Example 3 is shown in Figure 4 , Figure 5:The solid electrolyte is only adhered to the surface, and there is only sporadic filling inside. The conductivity of the final composite solid electrolyte membrane is 0.17 (E -3 s / cm, 25℃).
[0071] Comparative Example 4: Comparative Example 4 is compared with Example 1, except that the dispersants are replaced with sodium dodecylbenzene sulfonate, sodium tripolyphosphate, sodium sulfate of fatty alcohol polyoxyethylene ether, nonylphenol polyoxyethylene ether, polyvinyl pyrrolidone, and fatty alcohol polyoxyethylene ether, respectively, and the other operations are the same as those in Example 1 to prepare a composite electrolyte slurry. The other operations are the same as those in Example 1.
[0072] The results show that the composite electrolyte slurry prepared by the above dispersant will have obvious sedimentation and slight stratification, and serious sedimentation will occur if the dispersant is not added. This is because it is difficult to form a chemical bond with the small-particle LATP inorganic electrolyte when replaced with a dispersant without quaternary ammonium groups, making it difficult to ensure the dispersibility of small-particle and large-particle solid electrolytes.
[0073] Comparative Example 5: Compared with Example 1, the difference between Comparative Example 5 and Example 1 is that the timing of adding the sodium polyacrylate (PAA) binder solution is different. In Comparative Example 5, sodium polyacrylate (PAA) binder is added to the solid electrolyte slurry, and the mass percentage in the solid electrolyte slurry is 0.6%.
[0074] (1) Preparation of solid electrolyte slurry: The material ratios in the solid electrolyte slurry are 20% LATP inorganic electrolyte, 2% BYK-ET3000 dispersant, 0.6% sodium polyacrylate (PAA) binder, and the rest NMP solvent, totaling 100%; the small-particle LATP inorganic electrolyte in the LATP inorganic electrolyte accounts for 6% of the total mass of the solid electrolyte, and the rest is large-particle LATP inorganic electrolyte.
[0075] Pour 30% of the solvent into the high-speed mixer in proportion, start stirring and slowly add the dispersant and stir for 10-15 minutes, continue stirring (stirring speed is 15m / s) and slowly add small-particle and large-particle oxide solid electrolyte powders, add binder, increase the stirring line speed to 25m / s, add the remaining solvent and stir for 30 minutes before use.
[0076] (2) Preparation of solid electrolyte membrane: The high-pore polyolefin microporous membrane was fixed at both ends and completely immersed in the above-mentioned solid electrolyte slurry. After ultrasonic oscillation at 35°C with a power of 250 W for 10 min, it was taken out and completely dried at 55°C with far-infrared hot air. The far-infrared power was 200 W and the irradiation distance was 30 cm to obtain a composite solid electrolyte membrane.
[0077] Comparative Example 5 The cross section of the composite solid electrolyte membrane was observed by SEM to see whether there was bulk composite. Only a layer of solid electrolyte PAA adhered to the surface to form a barrier film on the surface, and the solid electrolyte could hardly enter the interior of the microporous membrane (see Figure 6 The conductivity of the composite solid electrolyte membrane is 0.07 (E -3 s / cm, 25℃).
[0078] The reason why the binder needs to be added later in Example 1 is that in order to better disperse the solid electrolyte powder of different particle sizes, the solid electrolyte and the microporous membrane are first compounded to the greatest extent in the first stage, and the PAA is used in the second part to fill the small gaps that may exist, and play a bonding role to increase its compactness. If used like the conventional method in Comparative Example 5, it will hinder the degree of compounding of the main material and the solid electrolyte powder with the microporous membrane to a certain extent, occupying the space that could have been given to the electrolyte powder, and reducing its ionic conductivity to a certain extent. Therefore, the present invention realizes that the main material occupies the gap of the microporous membrane to the maximum extent, and at the same time does not affect the adsorption of the solid electrolyte in the microporous membrane, but promotes ion conduction to a certain extent through the solid electrolyte itself.
[0079] Comparative Example 6: Compared with Example 1, Comparative Example 6 differs in that no sodium polyacrylate (PAA) binder is added, and other operations are the same as those in Example 1.
[0080] The composite solid electrolyte membrane prepared in Comparative Example 6 has obvious powdering phenomenon, and the conductivity is 0.33 (E -3 s / cm, 25℃).
[0081] Comparative Example 7: Compared with Example 1, the difference between Comparative Example 7 and Example 1 is that the amount of dispersant used is 0.3%, and other operations are the same as Example 1.
[0082] The composite solid electrolyte membrane prepared in Comparative Example 7 has a composite effect of containing voids in some areas and a conductivity of 0.29 (E -3 s / cm, 25℃).
[0083] Comparative Example 8: Compared with Example 1, the difference between Comparative Example 8 and Example 1 is that the amount of dispersant used is 5.0%, and other operations are the same as Example 1.
[0084] The conductivity of the composite solid electrolyte membrane prepared in Comparative Example 8 is 0.43 (E -3 s / cm, 25℃).
[0085] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a composite solid electrolyte membrane, characterized in that: Follow the steps below, (1) Preparation of solid electrolyte slurry: Pour 30-50% of solvent into a high-speed mixer in proportion, start stirring and add dispersant, continue stirring and add small-particle oxide solid electrolyte powder and large-particle oxide solid electrolyte powder, add the remaining solvent and stir for standby use; the proportions of the materials in the solid electrolyte slurry are 20-30% of the oxide solid electrolyte, 0.5-4.0% of the dispersant, and the rest is solvent, totaling 100%; the small-particle oxide solid electrolyte powder accounts for 5-10% of the total mass of the oxide solid electrolyte powder, and the rest is large-particle oxide solid electrolyte powder; the dispersant is a dispersant containing a quaternary ammonium group; the particle size of the small-particle oxide solid electrolyte powder is 50-80nm; the particle size of the large-particle oxide solid electrolyte powder is 150-200nm; the polymer microporous membrane is a polyolefin microporous membrane, the pore size range is 300-5000nm, and the porosity is greater than 65%; (2) Preparation of solid electrolyte membrane: The polymer microporous membrane is completely immersed in the above-mentioned solid electrolyte slurry, taken out after ultrasonic vibration, and completely dried by hot air with far infrared to obtain intermediate A. Intermediate A is further immersed in a binder solution, taken out after ultrasonic vibration, and completely dried in a hot air environment with far infrared.
2. The method for preparing the composite solid electrolyte membrane according to claim 1, characterized in that: The oxide solid electrolyte is a LATP inorganic electrolyte.
3. The method for preparing the composite solid electrolyte membrane according to claim 1, characterized in that: The dispersant containing a quaternary ammonium group is one of BYK-ET3000, BYK-ET3001, BYK-ET3002, BYK-ET3004, or a mixture of two or more thereof.
4. The method for preparing the composite solid electrolyte membrane according to claim 1, characterized in that: The solvent is NMP or a mixed solvent of NMP and acetone.
5. The method for preparing the composite solid electrolyte membrane according to claim 1, characterized in that: The ultrasonic vibration conditions are: 35~55℃ ultrasonic vibration with a power of 250~300W for 2~10min.
6. The method for preparing the composite solid electrolyte membrane according to claim 1, characterized in that: The specific conditions for far-infrared hot air drying are: far-infrared power is 200~300W, irradiation distance is 30~50cm, and far-infrared hot air is used for drying at 45~55℃.
7. The method for preparing the composite solid electrolyte membrane according to claim 1, characterized in that: The binder is sodium polyacrylate PAA, and the mass concentration of the binder solution is 0.5-5%.
8. A composite solid electrolyte membrane prepared according to the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Expanded polytetrafluoroethylene reinforced solid electrolyte membrane and preparation method thereof
CN115663273A
Organic-inorganic composite solid electrolyte membrane, preparation method thereof and solid-state battery
CN117855596A
Manufacturing method of anisotropic conductive film and anisotropic conductive film
JP2008027676A